Self-managing individual wellness for the health professional: A somatology perspective - Karien Henrico; Jeanette E. Maritz; Johan Bezuidenhout (AOSIS, 2019)
Background: Health professionals play a vital role in the stability and sustainability of any healthcare system. However, the well-documented long working hours, lack of wellness support structures, regular occurrence of burnout and low retention rates are concerning. Aim: The aim of this research study was to understand how a group of therapists self-manage their own individual wellness, to provide insight on how other health professionals, working in a demanding environment, could potentially address their individual wellness more effectively. Setting: The research was conducted in a private room at the place of participant employment, in two metropolitans in Gauteng, South Africa. Method: Qualitative, explorative, descriptive and contextual designs were used within the paradigm of constructivism. Purposive sampling was used to select participants. Data were collected through in-depth interviews, field notes and reflective practices, and analysed through open coding. Results: This study revealed disequilibrium between the theoretical knowledge and practical realities of therapists, and indicated that these therapists experience various personal obstacles that hinder the self-management of their individual wellness. Conclusions: Somatology therapists use various personal strategies that allow them to better self-manage their individual wellness. Individual wellness seems to be a personal phenomenon, indicating the need to self-reflect on personal perceptions of wellness, individual wellness obstacles and individual wellness strategies to effectively self-manage individual wellness.